Method for recycling and regenerating an iron-based polyanion cathode material
Patent Information
- Application Number
- CN202610957676.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-09
AI Technical Summary
然而,采用该方法制得的再生正极材料应用于钠离子电池时,其首次充放电容量仍有待进一步提高
[0025]优选地,所述热处理的时间为5~15h。
Smart Images

Figure CN122889875A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery recycling and regeneration technology, and more specifically, to a method for recycling and regenerating iron-based polyanion cathode materials. Background Technology
[0002] my country has abundant sodium resources, and both the positive and negative electrodes of sodium-ion batteries can use lower-cost aluminum foil as the current collector, giving sodium-ion batteries a significant cost advantage. Furthermore, sodium-ion batteries exhibit good rate performance and low-temperature performance, meeting the requirements for rapid charging and discharging and use in cold environments. Thanks to these advantages, sodium-ion batteries have been widely used in transportation, energy storage, and other fields.
[0003] Similar to lithium-ion batteries, sodium-ion batteries also experience capacity decay over long-term use due to structural degradation and loss of active materials, eventually becoming unusable. Improper disposal of large quantities of discarded sodium-ion batteries can cause serious environmental pollution and resource waste. Therefore, carrying out sodium-ion battery recycling has significant environmental and economic benefits. In sodium-ion batteries, the cathode material, as a core component, has high recycling value.
[0004] Prior art, disclosed in CN118231824A, provides a method for recycling and applying positive electrode materials from waste sodium-ion batteries. The method includes the following steps: S1. Completely discharging the waste sodium-ion battery, disassembling and separating it to obtain positive and negative electrode sheets and positive electrode powder; S2. Dispersing the positive electrode powder in water and adding it to a high-pressure reactor, then adding a sodium source and reducing agent, stirring, and carrying out a hydrothermal reaction; collecting the solid phase by centrifugation, washing and drying the solid phase to obtain precursor powder; S3. Heat-treating the precursor powder under an inert atmosphere to obtain regenerated positive electrode material. However, when the regenerated positive electrode material obtained by this method is applied to sodium-ion batteries, its initial charge-discharge capacity still needs further improvement.
[0005] Based on this, it is of great significance to develop a recycling method for iron-based polyanion cathode materials to improve the initial charging capacity of the recycled cathode materials. Summary of the Invention
[0006] The primary objective of this invention is to overcome the shortcomings or defects of existing methods for recycling and regenerating sodium-ion battery cathode materials, and to provide a method for recycling and regenerating iron-based polyanion cathode materials.
[0007] Another object of the present invention is to provide a regenerated cathode material obtained by the above-described recycling method.
[0008] Another object of the present invention is to provide the application of the above-mentioned recycled cathode material in sodium-ion batteries.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: A method for recycling and regenerating iron-based polyanion cathode materials includes the following steps: S1. Obtain the recovered iron-based polyanion cathode material powder; S2. Disperse iron-based polyanion cathode material powder in a mixed aqueous solution composed of reducing sodium salt and sodium hydroxide, and carry out a hydrothermal reaction to obtain an intermediate repair material after the reaction; S3. Mix the intermediate repair material with the carbon source evenly, and then heat-treat it in an inert atmosphere to obtain the regenerated cathode material; The mass of the mixed aqueous solution accounts for more than 60% of the total mass of the iron-based polyanion cathode material powder and the mixed aqueous solution; The concentration of reducing sodium salt in the mixed aqueous solution is 0.1~1 mol / L; the concentration of sodium hydroxide in the mixed aqueous solution is 0.5~4 mol / L.
[0010] This invention uses sodium hydroxide and reducing sodium salt as raw materials to prepare a mixed aqueous solution of a specific concentration. The inventors discovered that in this mixed aqueous solution, sodium hydroxide and reducing sodium salt have a synergistic effect; when they undergo a hydrothermal reaction with iron-based polyanion cathode material powder, they can cause Fe... 3+ Reduced to Fe 2+ At the same time, Na + It enters the polyanionic lattice and further purifies its lattice structure, thereby achieving effective lattice repair. Furthermore, when sodium hydroxide and reducing sodium salts coexist in aqueous solution at specific concentrations, they can effectively alleviate the decomposition of the polyanionic lattice by sodium hydroxide.
[0011] Preferably, the concentration of reducing sodium salt in the mixed aqueous solution is 0.1~0.5 mol / L.
[0012] Preferably, the concentration of sodium hydroxide in the mixed aqueous solution is 0.5~2 mol / L.
[0013] When the mass of the mixed aqueous solution accounts for a high proportion of the total mass of the iron-based polyanion cathode material powder and the mixed aqueous solution, although it has no impact on the repair effect, it increases the amount of mixed aqueous solution used, resulting in resource waste. Preferably, the mass of the mixed aqueous solution accounts for 60-80% of the total mass of the iron-based polyanion cathode material powder and the mixed aqueous solution.
[0014] In this invention, the method for obtaining the recycled iron-based polyanion cathode material powder can refer to the prior art, for example: immersing the waste sodium-ion battery in a sodium chloride solution until it is completely discharged, disassembling and separating it to obtain the cathode sheet, and scraping the iron-based polyanion cathode material powder from the cathode sheet.
[0015] Preferably, the iron-based polyanionic cathode material is one of sodium iron pyrophosphate, sodium iron pyrophosphate derivatives, sodium ferrous sulfate, or sodium ferrous sulfate derivatives.
[0016] In this invention, the sodium iron pyrophosphate derivative includes materials that are doped at Fe sites or have defects introduced and / or doped at PO4 sites.
[0017] In this invention, the sodium ferrous sulfate derivative includes materials that are doped at Fe sites or have defects introduced and / or doped at SO4 sites.
[0018] Preferably, the reducing sodium salt is one or more of sodium sulfite, sodium dithionite, sodium thiosulfate, sodium nitrite, or sodium iodide.
[0019] Preferably, the temperature of the hydrothermal reaction is 50~150℃.
[0020] Preferably, the hydrothermal reaction time is 1 to 10 hours.
[0021] Preferably, the hydrothermal reaction further includes centrifugation and drying steps.
[0022] In this invention, the carbon source can be a commonly used carbon source in the art, preferably one or more of starch, citric acid, glucose, polyethylene glycol or polyvinyl alcohol.
[0023] Preferably, the mass ratio of the carbon source to the intermediate remediation material is 5~15:100.
[0024] As is known to those skilled in the art, different iron-based polyanionic cathode materials require different heat treatment temperatures due to variations in their thermodynamic stability. For sodium iron pyrophosphate or its derivatives, the heat treatment temperature is preferably 500–580°C. For sodium ferrous sulfate or its derivatives, the heat treatment temperature is preferably 350–400°C.
[0025] Preferably, the heat treatment time is 5 to 15 hours.
[0026] The recycled cathode material obtained by the above recycling method is also within the scope of protection of this invention.
[0027] The application of the aforementioned recycled cathode material in sodium-ion batteries is also within the scope of protection of this invention.
[0028] Compared with the prior art, the beneficial effects of the present invention include: This invention provides a novel method for recycling and regenerating iron-based polyanion cathode materials. The invention uses sodium hydroxide and reducing sodium salt as raw materials to prepare a mixed aqueous solution of a specific concentration. This mixed aqueous solution is used as a remediation solution to react with iron-based polyanion cathode material powder. This process reduces ferric iron to ferrous iron while simultaneously replenishing sodium, reducing Fe / Na antisite defects, and purifying the crystal lattice structure. Furthermore, the coexistence of sodium hydroxide and reducing sodium salt at specific concentrations in the aqueous solution alleviates the decomposition effect of sodium hydroxide on the polyanion lattice, thereby improving the charging capacity of the regenerated cathode material.
[0029] The recycling and regeneration method provided by this invention has a simple preparation process and is safe and environmentally friendly. Attached Figure Description
[0030] Figure 1 The X-ray diffraction pattern is shown for the iron-based polyanion cathode material powder prepared in Example 1 of this invention.
[0031] Figure 2 The image shows the X-ray diffraction pattern of the regenerated electrode material prepared in Example 1 of this invention.
[0032] Figure 3 The image shows the charge-discharge curves of a sodium-ion battery assembled from the iron-based polyanion cathode material powder prepared in Example 1 of this invention.
[0033] Figure 4 This is a charge-discharge curve of a sodium-ion battery assembled from the regenerated electrode material prepared in Example 1 of the present invention.
[0034] Figure 5 This is a cycle test diagram of a sodium-ion battery assembled from the iron-based polyanion cathode material powder prepared in Example 1 of the present invention.
[0035] Figure 6 This is a cycle test diagram of a sodium-ion battery assembled from the regenerated electrode material prepared in Example 1 of the present invention.
[0036] Figure 7 This is the X-ray diffraction pattern of the regenerated electrode material prepared in Comparative Example 1 of the present invention.
[0037] Figure 8 This is a charge-discharge curve of the regenerated electrode material prepared in Comparative Example 1 of the present invention.
[0038] Figure 9 This is a cyclic test diagram of the regenerated electrode material prepared in Comparative Example 1 of the present invention. Detailed Implementation
[0039] The present invention will be further described below with reference to embodiments and comparative examples. These embodiments are merely typical descriptions of the present invention, but the present invention is not limited thereto. Unless otherwise specified, the test methods used in the following embodiments and comparative examples are conventional methods, and the raw materials and reagents used are commercially available from conventional commercial sources.
[0040] Example 1 This embodiment provides a method for recycling and regenerating iron-based polyanion cathode materials, including the following steps: S1. Place the waste sodium-ion battery with Na4Fe3(PO4)2P2O7 as the positive electrode material into an aqueous sodium chloride solution and immerse it until it is completely discharged. Disassemble and separate the positive electrode sheet, scrape off the powder on the surface of the positive electrode sheet, and after cleaning and drying, obtain iron-based polyanionic positive electrode material powder. S2. According to the concentration of sodium thiosulfate in the mixed aqueous solution being 0.2 mol / L and the concentration of sodium hydroxide being 1 mol / L, weigh out sodium thiosulfate and sodium hydroxide, dissolve them in water, stir and mix well to obtain a mixed aqueous solution; S3. According to the principle that the mass of the mixed aqueous solution accounts for 60% of the total mass of the iron-based polyanion cathode material powder and the mixed aqueous solution, weigh 10g of iron-based polyanion cathode material powder and 15g of mixed aqueous solution, stir and mix them evenly, and carry out hydrothermal reaction at 80℃ for 6 hours. After the reaction is completed, centrifuge and dry them in sequence to obtain intermediate repair material. S4. According to the mass ratio of carbon source to intermediate repair material of 10:100, the intermediate repair material obtained in step S3 is mixed with glucose evenly, and then heat-treated at 550°C for 12 hours in an inert atmosphere, and then cooled to obtain the regenerated cathode material.
[0041] Structural characterization X-ray diffraction characterization was performed on the iron-based polyanion cathode material powder and the regenerated cathode material prepared in this embodiment, and the results are as follows: Figure 1 and Figure 2 As shown.
[0042] from Figure 1 and Figure 2 It can be seen that the diffraction peaks of the iron-based polyanion cathode material powder prepared in this embodiment are broadened and impurity peaks appear, while the regenerated cathode material prepared in this embodiment is a pure phase.
[0043] Performance testing (1) Preparation of button cell batteries A button cell battery is prepared using the iron-based polyanionic cathode material powder or recycled cathode material obtained in this embodiment as the cathode material. The preparation method of the button cell battery specifically includes the following steps: S1. Dissolve 2g of positive electrode material, 0.25g of binder PVDF, and 0.25g of conductive agent acetylene black in 10mL of N-methylpyrrolidone, stir and mix well to prepare positive electrode slurry, coat it on aluminum foil with a coating machine, and dry it in a vacuum drying oven at 120℃ for 10h to obtain positive electrode sheet. S2. The positive electrode sheet obtained in step S1 is assembled with a sodium metal sheet, a glass fiber separator and an electrolyte into a button cell. The electrolyte is a 1 mol / L NaPF6 PC (propylene carbonate) / EMC (ethyl methyl carbonate) solution containing 4 wt% FEC (fluoroethylene carbonate).
[0044] (2) Charge and discharge test The button batteries prepared above were subjected to charge-discharge tests (voltage range 1.7~4.3V, current density 0.1C, 1C defined as 129mA / g) and cycle stability tests (100 cycles under 1C conditions). The results are as follows: Figures 3-6 As shown.
[0045] from Figure 3 and Figure 4 It can be seen that the initial charging capacity of the button battery assembled from iron-based polyanion cathode material powder is 85.5 mAh / g; while the initial charging capacity of the button battery assembled from recycled cathode material is 110.6 mAh / g. This indicates that the recycling and regeneration method of iron-based polyanion cathode material provided by the present invention has a good repair effect.
[0046] from Figure 5 and Figure 6 It can be seen that the capacity retention rate of the button battery assembled from iron-based polyanion cathode material powder is 93.5%; while the capacity retention rate of the button battery assembled from recycled cathode material is 98.0%. This indicates that the recycling and regeneration method of iron-based polyanion cathode material provided by the present invention has a good repair effect.
[0047] Example 2 This embodiment provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Embodiment 1, except that the mixed aqueous solution used is different. Specifically: S2. According to the concentration of sodium dithionite in the mixed aqueous solution being 0.1 mol / L and the concentration of sodium hydroxide being 0.5 mol / L, weigh out sodium dithionite and sodium hydroxide, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0048] The regenerated cathode material prepared in this embodiment was characterized by X-ray diffraction, and the characterization results were basically similar to those in Example 1. The regenerated cathode material prepared in this embodiment is a pure phase.
[0049] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0050] Example 3 This embodiment provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Embodiment 1, except that the mixed aqueous solution used is different. Specifically: S2. Weigh out sodium dithionite and sodium hydroxide according to the concentration of sodium dithionite being 0.5 mol / L and sodium hydroxide being 2 mol / L in the mixed aqueous solution, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0051] The regenerated cathode material prepared in this embodiment was characterized by X-ray diffraction, and the characterization results were basically similar to those in Example 1. The regenerated cathode material prepared in this embodiment is a pure phase.
[0052] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0053] Example 4 This embodiment provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Embodiment 1, except that the mixed aqueous solution used is different. Specifically: S2. According to the concentration of sodium dithionite in the mixed aqueous solution being 0.1 mol / L and the concentration of sodium hydroxide being 2 mol / L, weigh out sodium dithionite and sodium hydroxide, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0054] The regenerated cathode material prepared in this embodiment was characterized by X-ray diffraction, and the characterization results were basically similar to those in Example 1. The regenerated cathode material prepared in this embodiment is a pure phase.
[0055] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0056] Example 5 This embodiment provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Embodiment 1, except that the mixed aqueous solution used is different. Specifically: S2. Weigh out sodium iodide and sodium hydroxide according to the concentration of sodium iodide in the mixed aqueous solution being 0.2 mol / L and sodium hydroxide being 1 mol / L, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0057] The regenerated cathode material prepared in this embodiment was characterized by X-ray diffraction, and the characterization results were basically similar to those in Example 1. The regenerated cathode material prepared in this embodiment is a pure phase.
[0058] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0059] Example 6 This embodiment provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Embodiment 1, except that the carbon source used is different, specifically, glucose is replaced with an equal mass of citric acid.
[0060] The regenerated cathode material prepared in this embodiment was characterized by X-ray diffraction, and the characterization results were basically similar to those in Example 1. The regenerated cathode material prepared in this embodiment is a pure phase.
[0061] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0062] Example 7 This embodiment provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Embodiment 1. The difference lies in the ratio of the mass of the mixed aqueous solution to the total mass of the iron-based polyanionic cathode material powder and the mixed aqueous solution. Specifically, the mass of the mixed aqueous solution accounts for 80% of the total mass of the iron-based polyanionic cathode material powder and the mixed aqueous solution, that is, 10g of iron-based polyanionic cathode material powder and 40g of mixed aqueous solution are weighed and stirred evenly.
[0063] The regenerated cathode material prepared in this embodiment was characterized by X-ray diffraction, and the characterization results were basically similar to those in Example 1. The regenerated cathode material prepared in this embodiment is a pure phase.
[0064] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0065] Comparative Example 1 This comparative example provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Example 1, except that the mixed aqueous solution used is different. Specifically: S2. Weigh out sodium thiosulfate and phosphoric acid according to the concentration of sodium thiosulfate being 0.2 mol / L and phosphoric acid being 1 mol / L in the mixed aqueous solution, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0066] The regenerated cathode material prepared in this comparative example was characterized by X-ray diffraction. The characterization results are as follows: Figure 7 As shown.
[0067] from Figure 7 It can be seen that the diffraction peaks of the regenerated electrode material powder prepared in this comparative example are broadened and impurity peaks appear.
[0068] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in [Figure 1]. Figure 8 , Figure 9 See Table 1. The results show that the button battery assembled from the recycled cathode material prepared in this comparative example has an initial charge capacity of only 78.3 mAh / g and a capacity retention rate of only 84.8%.
[0069] Comparative Example 2 This comparative example provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Example 1, except that the mixed aqueous solution used is different. Specifically: S2. Weigh out sodium carbonate and sodium hydroxide according to the concentration of sodium carbonate in the mixed aqueous solution being 0.2 mol / L and the concentration of sodium hydroxide being 1 mol / L, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0070] The regenerated cathode material prepared in this comparative example was characterized by X-ray diffraction, and the characterization results were basically similar to those of Comparative Example 1. The diffraction peaks of the regenerated electrode material powder prepared in this comparative example showed broadening and the appearance of impurity peaks.
[0071] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0072] Comparative Example 3 This comparative example provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Example 1, except that the mixed aqueous solution used is different. Specifically: S2. Weigh out ferrous ammonium sulfate and sodium hydroxide according to the concentration of 0.2 mol / L and sodium hydroxide of 1 mol / L in the mixed aqueous solution, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0073] The regenerated cathode material prepared in this comparative example was characterized by X-ray diffraction, and the characterization results were basically similar to those of Comparative Example 1. The diffraction peaks of the regenerated electrode material powder prepared in this comparative example showed broadening and the appearance of impurity peaks.
[0074] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0075] Comparative Example 4 This comparative example provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Example 1, except that the mixed aqueous solution used is different. Specifically: S2. According to the concentration of sodium dithionite in the mixed aqueous solution being 0.2 mol / L and the concentration of sodium hydroxide being 0.4 mol / L, weigh out sodium dithionite and sodium hydroxide, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0076] The regenerated cathode material prepared in this comparative example was characterized by X-ray diffraction, and the characterization results were basically similar to those of Example 1. The regenerated cathode material prepared in this comparative example was a pure phase.
[0077] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0078] Comparative Example 5 This comparative example provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Example 1, except that the mixed aqueous solution used is different. Specifically: S2. Weigh out sodium dithionite and sodium hydroxide according to the concentration of sodium dithionite being 0.5 mol / L and sodium hydroxide being 5 mol / L in the mixed aqueous solution, dissolve them in water, stir and mix well to obtain a mixed aqueous solution.
[0079] The regenerated cathode material prepared in this comparative example was characterized by X-ray diffraction, and the characterization results were basically similar to those of Comparative Example 1. The diffraction peaks of the regenerated electrode material powder prepared in this comparative example showed broadening and the appearance of impurity peaks.
[0080] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0081] Comparative Example 6 This comparative example provides a method for recycling and regenerating iron-based polyanionic cathode materials, which is basically the same as that in Example 1. The difference lies in the proportion of the mass of the mixed aqueous solution to the total mass of the iron-based polyanionic cathode material powder and the mixed aqueous solution. Specifically, the mass of the mixed aqueous solution accounts for 44% of the total mass of the iron-based polyanionic cathode material powder and the mixed aqueous solution, that is, 10g of iron-based polyanionic cathode material powder and 8g of mixed aqueous solution are weighed and stirred evenly.
[0082] The regenerated cathode material prepared in this comparative example was characterized by X-ray diffraction, and the characterization results were basically similar to those of Example 1. The regenerated cathode material prepared in this comparative example was a pure phase.
[0083] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0084] Comparative Example 7 This comparative example provides a method for recycling and regenerating iron-based polyanion cathode materials, including the following steps: S1. Place the waste sodium-ion battery with Na4Fe3(PO4)2P2O7 as the positive electrode material into an aqueous sodium chloride solution and immerse it until it is completely discharged. Disassemble and separate the positive electrode sheet, scrape off the powder on the surface of the positive electrode sheet, and after cleaning and drying, obtain iron-based polyanionic positive electrode material powder. S2. Weigh 10g of iron-based polyanion cathode material powder and 15g of sodium hydroxide solution with a concentration of 1mol / L, stir and mix well, then add 15g of sodium thiosulfate solution with a concentration of 0.2mol / L, stir and mix well, and carry out hydrothermal reaction at 80℃ for 6 hours. After the reaction is completed, centrifuge and dry in sequence to obtain intermediate repair material. S3. The intermediate repair material obtained in step S3 is mixed with glucose at a mass ratio of 10:100, and then heat-treated at 550°C for 12 hours in an inert atmosphere. After cooling, the regenerated cathode material is obtained.
[0085] The regenerated cathode material prepared in this comparative example was characterized by X-ray diffraction, and the characterization results were basically similar to those of Comparative Example 1. The diffraction peaks of the regenerated electrode material powder prepared in this comparative example showed broadening and the appearance of impurity peaks.
[0086] Referring to the performance testing method in Example 1, its initial charging capacity and capacity retention rate were measured, and the results are shown in Table 1.
[0087] Table 1. Initial charge capacity and capacity retention of button batteries prepared in each embodiment and comparative example.
[0088] As shown in Table 1, the recycling and regeneration method provided by the present invention can effectively realize the recycling and regeneration of waste sodium-ion batteries, and the repaired and regenerated cathode material has good charging capacity and cycle performance.
[0089] Comparing Example 1 and Comparative Examples 1-3, it can be seen that only when the mixed aqueous solution is sodium hydroxide and reducing sodium salt can Fe be produced. 3+ Reduced to Fe 2+ At the same time, make Na + By entering the lattice of the polyanion and further purifying its lattice structure without destroying the lattice, the lattice in the iron-based polyanion cathode material can be effectively repaired.
[0090] Comparing Example 1 and Comparative Example 4, it can be seen that when the concentration of sodium hydroxide in the mixed aqueous solution is less than 0.5 mol / L, sodium hydroxide and reducing sodium salt cannot form a synergistic effect, resulting in a poorer repair effect.
[0091] Comparing Example 1 and Comparative Example 5, it can be seen that when the concentration of sodium hydroxide in the mixed aqueous solution is higher than 4 mol / L, sodium hydroxide and reducing sodium salt cannot form a synergistic effect, making it difficult to alleviate the decomposition effect of sodium hydroxide on the crystal lattice, resulting in a decrease in the repair effect.
[0092] Comparing Example 1 and Comparative Example 6, it can be seen that when the amount of the mixed aqueous solution used is small, its repair effect is difficult to be fully exerted, resulting in a decrease in the repair effect.
[0093] Comparing with Comparative Example 7, it can be seen that if the sodium hydroxide solution and the reducing sodium salt solution are not added to the system simultaneously, they cannot form a synergistic effect, making it difficult to alleviate the decomposition effect of sodium hydroxide on the crystal lattice, resulting in a decrease in the repair effect.
[0094] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for recycling and regenerating iron-based polyanionic cathode materials, characterized in that, Includes the following steps: S1. Obtain the recovered iron-based polyanion cathode material powder; S2. The iron-based polyanion cathode material powder is dispersed in a mixed aqueous solution composed of reducing sodium salt and sodium hydroxide, and a hydrothermal reaction is carried out to obtain an intermediate repair material after the reaction. S3. Mix the intermediate repair material with the carbon source evenly, and then heat-treat it in an inert atmosphere to obtain the regenerated cathode material; The mass of the mixed aqueous solution accounts for more than 60% of the total mass of the iron-based polyanion cathode material powder and the mixed aqueous solution; The concentration of reducing sodium salt in the mixed aqueous solution is 0.1~1 mol / L; the concentration of sodium hydroxide in the mixed aqueous solution is 0.5~4 mol / L.
2. The recycling and regeneration method according to claim 1, characterized in that, The concentration of reducing sodium salt in the mixed aqueous solution is 0.1~0.5 mol / L.
3. The recycling method according to claim 1, characterized in that, The iron-based polyanionic cathode material is one of sodium iron pyrophosphate, sodium iron pyrophosphate derivatives, sodium ferrous sulfate, or sodium ferrous sulfate derivatives.
4. The recycling method according to claim 1, characterized in that, The reducing sodium salt is one or more of sodium sulfite, sodium dithionite, sodium thiosulfate, sodium nitrite, or sodium iodide.
5. The recycling method according to claim 1, characterized in that, The temperature of the hydrothermal reaction is 50~150℃.
6. The recycling method according to claim 1, characterized in that, The hydrothermal reaction time is 1 to 10 hours.
7. The recycling method according to claim 1, characterized in that, The mass of the mixed aqueous solution accounts for 60-80% of the total mass of the iron-based polyanionic cathode material powder and the mixed aqueous solution.
8. The recycling method according to claim 1, characterized in that, The mass ratio of the carbon source to the intermediate remediation material is 5~15:
100.
9. The recycled cathode material obtained by any of the recycling methods described in claims 1 to 8.
10. The application of the recycled cathode material according to claim 9 in a sodium-ion battery.
Citation Information
Patent Citations
Recycling method and application of waste sodium-ion battery positive electrode material
CN118231824A